2006
DOI: 10.2307/30032477
|View full text |Cite
|
Sign up to set email alerts
|

Alloxan-Induced and Insulin-Resistant Diabetes Mellitus Affect Semen Parameters and Impair Spermatogenesis in Male Rats / Diabète sucré provoqué par l'alloxane aussi bien que le diabète insulinorésistant influent sur les paramètres du sperme et entravent la spermatogenèse chez les rats mâles

Abstract: The purpose of this study was to determine the effects of diabetes mellitus and insulin resistance on semen parameters, histology of reproductive organs and serum concentrations of testosterone and luteinizing hormone (LH). Male Sprague-Dawley rats weighing 180 - 200g were made diabetic by intravenous injection of alloxan (40 mg/kg): and insulin resistant by chronic fructose feeding (25% fructose) for 12 weeks. Rats were anaesthetized, followed by laparatomy. Blood was obtained by cardiac puncture for measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The present study has demonstrated body weight loss in diabetic animals that is in line with other studies, which reported weight loss in diabetic cases 8,30. There are many studies which have reported the beneficial effects of some plant extracts31-33 on the body weight of diabetics.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study has demonstrated body weight loss in diabetic animals that is in line with other studies, which reported weight loss in diabetic cases 8,30. There are many studies which have reported the beneficial effects of some plant extracts31-33 on the body weight of diabetics.…”
Section: Discussionsupporting
confidence: 92%
“…Impairment of sexual behavior,5 semen quality,2 and ejaculation7 are the most common reproductive consequences in diabetic men. Disrupted spermatogenesis and oligozoospermic cases of diabetes have also been reported 8,9. Decreased sperm motility1 and disturbance in gonadal10 and gonadotropin1 hormones were reported in diabetics as well.…”
Section: Introductionmentioning
confidence: 97%
“…While there are studies showing testicular and epididymal structural, morphological and histological changes, such as reduction in organ size and lower diameters of the tubules and lumen (Seethalakshmi et al 1987;Cameron et al 1990;Hassan et al 1993;Soudamani et al 2005;Scarano et al 2006;Amaral et al 2009) and spermatogenic impairment in diabetic animals (Kühn-Velten et al 1984;Gondos and Bevier 1995;Arikawe et al 2006;Amaral et al 2009;Kianifard et al 2012;Wankeu-Nya et al 2013;Kyathanahalli et al 2014;Wankeu-Nya et al 2013), others failed to detect any changes at these levels (Navarro-Casado et al 2010). The conflicting data may result from the fact that when assessing the in vivo effects of DM on spermatogenesis there are several factors that are difficult to control and that present variable responses, such as altered hormonal regulation, inflammation, oxidative stress and other alterations associated with the disease that might contribute to a general dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…Although the existing literature suggests that diabetic conditions might affect spermatogenesis (Gondos and Bevier 1995;Arikawe et al 2006;Amaral et al 2009;Kianifard et al 2012;Wankeu-Nya et al 2013;Kyathanahalli et al 2014;Portela et al 2015), the mechanisms accountable for the observed male reproductive dysfunction remain poorly understood. Therefore, our goal was to determine whether spermatogenesis progression is affected by the sole exposure to high glucose levels, the foremost recognised signature of DM and the major effector of the disease pathophysiology.…”
Section: Introductionmentioning
confidence: 97%
“…About 0.5–1 ml of blood was aspirated from the left ventricle and centrifuged at 300 g for 20 min. Serum was carefully aspirated by a fine Pasteur pipette into a clean centrifuge tube, sealed, and kept at −20°C until the time of hormone measurement [17]. Serum testosterone level was measured using an ELISA kit (IBL Company, Japan), as recommended by the manufacture.…”
Section: Methodsmentioning
confidence: 99%